Four new flavonoids with DGAT inhibitory activity from Psoralea corylifolia. (December 2018) - Li, Hao-Ze; Meng, Xiao; Jiang, Yi-Yu; Lin, Xin; Xiong, Da-Xi; Wang, Dong; Lee, Hyun-Sun; Cui, Long
Graphical abstract: Highlights: Compounds 1–4 were isolated from Psoralea corylifolia. Compounds 1, 6, 7, 10 and 11 exhibited DGAT1 inhibitory activity. Psoralea corylifolia may have potential for the treatment of type II diabetes and obesity. Abstract: Four new compounds, 3′'-methoxy-bavacoumestan C (1 ), 6, 7-furanbavachinone B (2 ), 3, 4- furanbavachalcone A (3 ) and 4, 5- furanbavachalcone A (4 ), together with seven known flavonoids were isolated from the Psoralea corylifolia. Their structures were determined by extensive spectroscopic and physicochemical analyses. All the compounds (1 –11 ) were evaluated for in vitro inhibitory activity against DGAT. Among them, compounds1, 6, 7, 10 and11 were found to exhibit selective inhibitory activity on DGAT1with IC50 values ranging from 78.5 ± 1.7 to 153.4 ± 1.5 μM.